Monetary policy implementation and the federal funds rate - Nautz, Dieter; Schmidt, Sandra (Journal of Banking & Finance, 2009)
This paper investigates how the implementation of monetary policy affects the dynamics and the volatility of the federal funds rate. Since the early 1980s, the most important changes in the Fed’s conduct of monetary policy refer to the role of the federal funds rate target and the reserve requirement system. We show that the improved communication and transparency regarding the federal funds rate target has significantly increased the Fed’s influence on the federal funds rate since 1994. By contrast, the declining role of required reserves in the US has contributed to higher federal funds rate volatility. Our results suggest that the introduction of remunerated required reserves will further enhance the controllability of the federal funds rate.